'I know death. He's got many faces:' The presence of death in young peoples' media. (2nd October 2021) - Schott, Gareth
ABSTRACT: The repeated use of death as a plot point or dramatic turn in the context of fictional storytelling might appear shallow and (occasionally) distasteful. Yet, the normative presence of death in drama serve as constant reminders that life and lives (including our own) will undoubtedly end. Death awareness and the power and intensity of death over life shifts across a lifespan and over time. This Special Edition holds an interest in the ways death remains in constant attendance, often as a veiled and transformed concept in our everyday lives (e.g. humour and entertainment). It specifically considers engagements with concepts of death accessed by young people, or exchanges (e.g. memes) across media platforms adopted by young people. Scholars were invited to give consideration to the manner in which death is woven into the stories and images that young people consume (often independently), and changing patterns of communication (the web is awash in death jokes and memes mocking our fragile mortality) and language in an attempt to stay abreast of the transformative nature and breadth of death as an inescapable concept.